Efeito do tratamento periodontal básico no controle glicêmico e da inflamação de pacientes com Diabetes Mellitus tipo 1 e tipo 2: Ensaio Clínico Controlado - Lopes, Claudia Camila Peruzzo (2016)
Periodontitis is often associated with diabetes mellitus (DM) and can be considered a chronic complications. Growing evidences suggests that periodontal disease has an adverse effect on glycemic control and an active role in the pathophysiology of complications related to DM, as in type 1 diabetes mellitus as in type 2 diabetes mellitus. Objective: Compare the response of basic periodontal therapy in diabetes patients with diabetes type 1 and type 2. Methodology: We selected 70 patients with periodontitis, these were divided into three groups: Control group (systemically healthy patients); Group test 1 (patients with type 1 diabetes mellitus); Group test 2 (patients with type 2 diabetes mellitus). The groups received basic periodontal treatment after clinical examination. The analyzis were performed at 0, 3 and 6 months, clinical parameters including periodontal and gingival crevicular amount of fluid. They were measured glycated hemoglobin (HbA1c) and prostaglandin E2 concentration. Results: There was an improvement in all clinical periodontal parameters evaluated in both groups as well as the amount of gingival crevicular fluid. It occurred more significant decrease (p<0,05) in HbA1c and PGE2 expression in group test 1, after 6 months. Conclusion: The basic periodontal treatment was more effective for glycemic control in patients with type 1 diabetes mellitus